Effects of omalizumab on eosinophil cationic peptide, 25-hydroxyvitamin-D, IL-1β and sCD200 in cases of Samter's syndrome: 36 months follow-up. (August 2013) - Yalcin, Arzu Didem; Uçar, Seçil; Gumuslu, Saadet; Strauss, Ludwig G.
Abstract Contex: The historic triad of nasal polyposis, asthma and intolerance to aspirin and related chemicals, recently designated as Samter's syndrome, is an inflammatory condition of unknown pathogenesis. This study surveyed the levels of chosen serum eosinophil cationic peptide (ECP), soluble CD200 (SCD200), interleukin (IL)-1β, high sensitive C-reactive protein (hs-CRP) and 25-hydroxyvitamin-D (25(OH)D) in the aspirin-induced asthmatic patients treated with anti-IgE therapy to investigate their roles in the pathogenesis of disease perpetuation and anti-IgE therapy's impact on them. Methods: Medical history, lung function tests and measurement of fractional exhale nitric oxide concentrations were performed on the same day. Concentrations of IL-1β and SCD200 in the serum samples were quantified using ELISA kits. Total and specific IgE and hs-CRP levels were enumerated by fluoroenzyme immunoassay. Serum levels of 25(OH)D were quantified by a radioimmunoassay. Results: We had three patients of severe persistent allergic asthma with Samter's syndrome. Levels of total IgE, ECP, fractional exhale nitric oxide concentrations, SCD200, IL-1β and hs-CRP were decreased while 25(OH)D was increased after starting the treatment of anti-IgE. Conclusions: To our knowledge, this is the first time an association between omalizumab use and Samter's syndrome has been documented. As a conclusion allergic nasal symptoms (sneezing, postnasal drip) and asthma symptoms were decreased in patients, but no change was seen on nasal polyposis development after omalizumab treatment.